Microstructure and Damping Property of Polyurethane Composites Hybridized with Ultraviolet Absorbents - Jiang Chang; Bing Tian; Li Li; Yufeng Zheng (Advances in Materials Science and Engineering)
This article investigated the microstructure and damping property of TPU composites with different contents of ultraviolet absorbents. It can be found that the ultraviolet absorbents formed fiber-shaped precipitations in the TPU matrix. The UV-328 was randomly distributed in the matrix and exhibited a weak interfacial bonding with the matrix. In comparison, the UV-329 was well embedded in the matrix and formed a relatively better interfacial bonding and compatibility with the TPU matrix. The damping factor tanδ of both 328-composites and 329-composites had been reduced gradually with increasing content of ultraviolet absorbents at the glass transition temperature range due to the fact that the ultraviolet absorbents were in the crystalline state which decreased the volume content of the viscoelastic TPU matrix. But the tanδ increased at the temperature range of higher than the glass transition temperature, which should be related to the dominance of interfacial frictions between the ultraviolet absorbents and the matrix on the energy absorption.